Ethics of Knowledge in Scientific Narratives: Moral Conflicts in J. Robert Oppenheimer’s Life in American Prometheus - Lagraa ,Fulla; Naoumi, Mohamed (Faculty of Letters and Foreign Languages Department of English, 2025)
Knowledge has always played a dual role in human history, serving both as a source of progress and as a cause of destruction. This dissertation investigates the ethical dimension of knowledge by examining the life of J. Robert Oppenheimer as represented in American Prometheus and contrasting it with Albert Einstein’s moral stance. The central problem addressed is whether knowledge can exist independently of virtue. To explore this issue, the study adopts a qualitative literary–philosophical approach. Aristotle’s virtue ethics—particularly the concepts of the Golden Mean, phronēsis (practical wisdom), and eudaimonia (human flourishing)—serves as the primary theoretical framework. The biography American Prometheus is used as the main text, supported by additional works on ethics and science. The findings reveal that Oppenheimer, despite his intellectual brilliance, represents the tragedy of knowledge pursued without virtue, while Einstein illustrates knowledge guided by moral responsibility. The study concludes that knowledge is never morally neutral; it must always be connected to virtue if it is to serve humanity responsibly